2019
DOI: 10.1038/s41379-018-0105-8
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma within anorectal fistulae: different clinicopathological characteristics between Crohn's disease-associated type and the usual type

Abstract: Adenocarcinoma within anorectal fistulae is rare and is sometimes associated with Crohn's disease. Crohn's disease-associated adenocarcinoma within anorectal fistulae has a poor prognosis; however, little is known about the clinicopathological differences between Crohn's disease-associated adenocarcinoma within anorectal fistulae and usual adenocarcinoma within anorectal fistulae. We retrospectively searched patients' charts and pathology archives at Tokyo Yamate Medical Center and Tokyo Medical and Dental Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The major histologic type of anorectal fistula cancer has been reported to be mucinous cancer [17]. Our study also found that mucinous cancer was the most frequent type of histology.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The major histologic type of anorectal fistula cancer has been reported to be mucinous cancer [17]. Our study also found that mucinous cancer was the most frequent type of histology.…”
Section: Discussionsupporting
confidence: 75%
“…It can be speculated that FDG is more likely to accumulate in anorectal fistula cancer, unlike normal mucinous cancer, because the tumor contains sites of inflammation [20]. Kodama et al report that anorectal fistula cancer associated with Crohn's disease has a worse prognosis than usual anorectal fistula cancer [17]. It has been reported that the expression of epithelial-to-mesenchymal transition-related protein is enhanced in the anorectal fistula cancer in Crohn's disease, thus increasing the likelihood for metastasis [21].…”
Section: Discussionmentioning
confidence: 99%
“…8 Other adenocarcinoma subtypes have been identified, including mucinous and tubular, with mucinous being the most common. 9,10 In the available literature, tubular carcinoma has been associated with lower grade tumors, though there have been very few reported cases available. 9 Mucinous adenocarcinomas meanwhile have been shown to have deeper invasion on histology when compared with tubular adenocarcinomas.…”
Section: Histology/pathogenesismentioning
confidence: 99%
“…28 Regarding prognosis, Kodama et al found that anal adenocarcinoma arising from CD-related fistula appears to behave significantly different when compared with anal cancer arising from a non-CD fistula and have suggested that it should be categorized as its own entity. 9 Its unique behavior and features have been identified as the main reason behind the poor prognosis. When compared with non-CD FAAC, anal cancer arising from CD-related fistula exhibits lower overall survival rate.…”
Section: Staging and Prognosismentioning
confidence: 99%
“…Although the risk of colorectal cancer (CRC) has been well described, the risk of CRC in diverted bowel segments is lacking, and the current risk remains unclear [1]. Typically, CDassociated cancers present in advanced stages are poorly differentiated and have a worse prognosis than usual adenocarcinoma [2][3][4][5]. For this reason, surveillance colonoscopy is necessary to detect cancer at an early stage.…”
Section: Introductionmentioning
confidence: 99%